Answer:
20
Step-by-step explanation:
(f + g)(x) = f(x) + g(x)
f(x) + g(x) = 3x² - 2 + 4x + 2 = 3x² + 4x
Substitute x = 2 into f(x) + g(x)
(f + g)(2) = 3(2)² + 4(2) = (3 × 4) + 8 = 12 + 8 = 20
Answer:
25%
Step-by-step explanation:
25% of 60 is 15 because 15 is 1/4 of 60 and 1/4 is 25%
Answer:
5 + g
Step-by-step explanation:
The sum of 5 and g,
5 + g
Answer:
= 105(x+2)/33-x
Step-by-step explanation:
Given the expression
[3(x+2)*10*7]÷70 - 2(x+2)
= 3(x+2)*70÷70 - 2(x+2)
= 210(x+2)/70-2x-4
= 210(x+2)/66-2x
= 210(x+2)/2(33-x)
= 105(x+2)/33-x
Answer:
∠ XZY ≈ 23.6°
Step-by-step explanation:
Using the sine ratio in the right triangle, that is
sinXZY =
=
=
, then
∠ XZY =
(
) ≈ 23.6° ( to 1 dec. place )